2017
DOI: 10.4067/s0718-48082017000200141
|View full text |Cite
|
Sign up to set email alerts
|

Eating behaviors in a male and female community sample: psychometric properties of the DEBQ

Abstract: the aim of this study was to assess the psychometric properties of the Dutch eating Behavior Questionnaire (DeBQ) in a community sample of chilean adults. the sample comprised 627 participants who completed a battery of questionnaires. the mean age of the sample was 36.07 years (sD =12.49), and 66.2% of them were women. Mean body mass index (BMi) was 25.61 kg/m 2 (sD =4.20). item analysis suggested that one item yielded very low corrected item-total correlation. the internal structure analysis revealed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…Cuestionario Holandés de Conducta Alimentaria (DEBQ, por sus siglas en inglés; Van Strien, Frijters, Bergers y Defares, 1986), retomando dos de las subescalas de la versión traducida al español por Bach (2002) y adaptada para Chile por Andrés, Oda-Montecinos y Saldaña (2017). La subescala Ingesta emocional (IE) fue utilizada para evaluar la presencia de conductas alimentarias que pueden estar influenciadas por estados emocionales; y la subescala Restricción alimentaria (RA) para evaluar la presencia de conductas relacionadas con el CPC.…”
Section: Resultsunclassified
“…Cuestionario Holandés de Conducta Alimentaria (DEBQ, por sus siglas en inglés; Van Strien, Frijters, Bergers y Defares, 1986), retomando dos de las subescalas de la versión traducida al español por Bach (2002) y adaptada para Chile por Andrés, Oda-Montecinos y Saldaña (2017). La subescala Ingesta emocional (IE) fue utilizada para evaluar la presencia de conductas alimentarias que pueden estar influenciadas por estados emocionales; y la subescala Restricción alimentaria (RA) para evaluar la presencia de conductas relacionadas con el CPC.…”
Section: Resultsunclassified
“…In our study population, we found higher scores for external eating compared with emotional or restrained eating; thus, individuals tend to eat more in response to external stimuli (i.e., the taste of food), regardless of feelings of hunger or satiety [ 50 ]. Previous studies have associated higher scores for emotional, external, and restrained eating scales of the DEBQ questionnaire with unhealthy eating patterns, being overweight, and unfavorable emotional states [ 51 , 52 , 53 ]. Our research has also shown that women tend to score higher on emotional and restrained eating behaviors compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…DEBQ has been used as a reliable assessment tool, with a robust structure that provides consistent information, adequate for the target population (adults/children, women/men, normal weight/obesity, from various cultures) and which has proved valid for the specific purpose for which it was created. It has a good internal consistency measured in multiple studies and variate settings by consistent statistical operations (Cronbach's coefficient alpha for reliability, analysis of its internal structure using exploratory structural equation modelling) [39,[52][53][54].…”
Section: Introductionmentioning
confidence: 99%